Basketball shooting: A science-based approach to coaching - Erculj, F.; Zovko, V. (Schriften zur Sportwissenschaft, 162, 2022)
This scientific monograph is a result of research work in the area of the study of the kinematics of a shot at the basket, which has been the central focus of the authors Frane Erculj and Matej Supej in the last decade. Along with the development of science and the profession, the technology used by the authors and their colleagues in their scientific and research work has also developed and changed.